Preparation and Kinetic Studies of Cross-Linked Chitosan Beads Using Dual Crosslinkers of Tripolyphosphate and Epichlorohydrin for Adsorption of Methyl Orange - Akhmad Sabarudin; Armeida D. R. Madjid (The Scientific World Journal)
Preparation of cross-linked chitosan beads using dual crosslinkers of tripolyphosphate (TPP) and epichlorohydrin (ECH) for the adsorption and kinetic studies of methyl orange (MO) had been carried out. FTIR spectra showed that TPP could act as the protecting agent of the NH2 group of chitosan and ECH reacted with the primary hydroxyl group of chitosan. Various concentrations of TPP, ECH, and immersing time in the TPP solution for bead formation were studied. The effect of pH and kinetics of adsorption were investigated to define the mechanism of adsorption and rate-limiting step. As a result, pH 3, 10% (w/v) TPP, 5% (v/v) ECH, and 12 h immersing time in TPP were selected as the optimum conditions for preparing the beads as indicated by the highest adsorption amount of MO. The cross-linked chitosan beads’ adsorption capacity for MO under optimum condition was found to be 79.55 mg/g with the adsorption rate constant (k) of 1.29 × 10−3/min. Furthermore, it was found that a low concentration of ECH could maintain the stability of chitosan in acidic conditions, whereas the concentration of TPP and immersing time controlled pore size and morphology of chitosan beads. The mechanism of adsorption of MO was controlled by the pore and rigidity of cross-linked chitosan beads. Bulk diffusion acted as a rate-limiting step, and a high concentration of MO inhibited diffusion and adsorption itself.